Titanium carbide / bismuth oxyiodide / bismuth phosphate-based photoelectrochemical sensor for dopamine detection and preparation method of titanium carbide / bismuth oxyiodide / bismuth phosphate-based photoelectrochemical sensor

By constructing titanium carbide/bismuth iodide/bismuth phosphate materials of Schottky junction and P-N junction, the problems of low sensitivity and poor selectivity of existing dopamine detection methods are solved, and rapid and highly selective dopamine detection is achieved.

CN119534571AActive Publication Date: 2025-02-28ZHEJIANG UNIV OF TECH
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411713780.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-27
Publication Date
2025-02-28
Estimated Expiration
2044-11-27

AI Technical Summary

Technical Problem

The existing dopamine detection methods have problems such as low sensitivity, poor selectivity, high cost and susceptibility to interference, making it difficult to achieve rapid and highly selective detection.

Method used

The Schottky junction and P-N junction were constructed using titanium carbide/bismuth iodide/bismuth phosphate (BT/BiPO4)-based materials to promote the separation and transfer of photogenerated electron-hole pairs and improve the detection performance of photoelectrochemical sensors.

Benefits of technology

It realizes rapid and highly selective detection of dopamine, has good sensitivity and linear response, and can accurately detect dopamine in the range of 0.01 to 10 mM.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure HDA0005156409690000011
    Figure HDA0005156409690000011
  • Figure HDA0005156409690000012
    Figure HDA0005156409690000012
  • Figure HDA0005156409690000013
    Figure HDA0005156409690000013
Patent Text Reader

Abstract

The invention discloses a titanium carbide / bismuth oxyiodide / bismuth phosphate-based photoelectrochemical sensor for dopamine detection and a preparation method of the titanium carbide / bismuth oxyiodide / bismuth phosphate-based photoelectrochemical sensor. The photoelectrochemical sensor is prepared by forming a film on the surface of a glassy carbon electrode by using a titanium carbide / bismuth oxyiodide / bismuth phosphate (BT / BiPO4) composite material; the BT / BiPO4 composite material has good photoresponse, and rapid electron transfer provides high sensitivity for detection of dopamine; the photoelectrochemical sensor disclosed by the invention is applied to dopamine detection, is high in sensitivity and has good linear response in a range of 0.01-10mM.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of photoelectrochemical sensor materials and preparation and application thereof, and specifically relates to a titanium carbide / bismuth oxyiodide / bismuth phosphate (BT / BiPO4) based photoelectrochemical sensor for dopamine detection and a preparation method thereof. Background Art

[0002] Dopamine (DA) is an excitatory chemical neurotransmitter that regulates the physiological activities transmitted by the cerebral cortex and plays an important regulatory role in many neurological diseases. DA in the human body controls human physiological characteristics. Once the DA concentration fluctuates dramatically, it is easy to cause neurological diseases such as Parkinson's disease, schizophrenia, depression, etc. However, the current level of medical technology cannot effectively treat these diseases. The occurrence of most mental illnesses is closely related to abnormal dopamine concentrations. Therefore, monitoring the dopamine concentration in the human body is of great help to clinical treatment, and it is crucial to manufacture a sensor with high sensitivity and high selectivity for detecting dopamine. At present, the methods for detecting dopamine concentration include high-performance liquid chromatography (HPLC), chemiluminescence, spectrophotometry, electrochemical method, etc. These methods have the disadvantages of requiring the use of expensive instruments and equipment, relatively high cost, and low sensitivity. The electrochemical method is low in cost, but it is easily interfered by dopamine-like electroactive substances such as AA and UA, has poor selectivity, and relatively low sensitivity. Therefore, it is very important to explore a fast and sensitive method for detecting dopamine.

[0003] In recent years, photoelectrochemical (PEC) sensors have rapidly emerged and have become a new type of sensor that has attracted much attention due to their unique advantages. PEC sensors convert optical signals into electrical signals through biorecognition elements and signal converters, and use the changes in photocurrent signals to achieve qualitative and quantitative analysis of the target. Compared with fluorescence, electrochemistry and electroluminescence technologies, PEC detection technology has lower background signals and higher detection sensitivity due to its independent excitation light source and signal acquisition system, so it has become an analytical technology with great application value. However, the preparation of the photoelectrochemical sensing platform requires photoactive nanomaterials with efficient visible light driving characteristics, so it is very important to find a photoactive nanomaterial for photoelectrochemical sensing of dopamine.

[0004] Titanium carbide (Ti3C2T x ) is one of the most widely used MXenes (transition metal carbides, nitrides or carbonitrides), which has many advantages, including conductivity, mechanical properties, huge surface area, and especially compatibility with other nanomaterials. The above advantages make Ti3C2T x It is widely used in electrocatalysis, energy storage batteries, electrochemical sensors and other fields, but so far, Ti3C2Tx The research on PEC sensing technology is still in its infancy. It is worth noting that MXene (especially -OH-functionalized Ti3C2T4) is a promising candidate for the development of PEC sensing technology. x ) can effectively conduct electricity and can separate and transport Ti3C2T x / photogenerated carriers in semiconductor heterostructures and then in Ti3C2T x A built-in electric field is generated between the Ti3C2T x The accordion-like multilayer structure itself has an inherent negatively charged surface and active OH-Ti sites, and first-principles calculations show that Ti3C2T x The Schottky barrier is close to 0, and the Ti3C2Tx-based composite materials can be used in photoelectrochemical sensors to achieve the detection of targets.

[0005] Among many semiconductor materials, bismuth-based materials are low-cost, non-toxic, and have narrow band gaps. In addition, the 6s orbital of bismuth and the 2p orbital of oxygen give them superior optical and electrical properties. Bismuth-based materials are widely used in photocatalysis and the preparation of photoelectrochemical sensors. Bismuth oxyiodide (BiOI) is a typical narrow band gap with good visible light capture ability. However, due to the poor conductivity of BiOI, the easy recombination of photogenerated electron-hole pairs and the poor carrier separation efficiency, its application in the field of PEC is limited.

[0006] The titanium carbide / bismuth iodide / bismuth phosphate material prepared by the present invention constructs a Schottky junction by titanium carbide / bismuth iodide material, and then introduces a bismuth phosphate material to construct a PN junction, which promotes the separation of photogenerated electron-hole pairs and inhibits the recombination of photogenerated electron-hole pairs, thereby increasing the photocurrent. The combination of bismuth iodide with titanium carbide and bismuth phosphate significantly improves the PEC activity, improves the PEC performance by accelerating the transfer of photogenerated electrons, and realizes rapid and highly selective dopamine detection. Summary of the invention

[0007] The present invention provides a BT / BiPO4 material and a preparation method thereof. The BT / BiPO4 material can be further prepared into a photoelectrochemical sensor for dopamine detection.

[0008] The technical solution of the present invention is as follows:

[0009] A method for preparing BT / BiPO4 material comprises the following steps:

[0010] (1) Bi(NO3)3·5H2O solution was added dropwise to KI solution and stirred for 1 h. Then Ti3C2 powder was added and ultrasonicated (300 W) for 10 min to obtain a mixed solution.

[0011] The mass ratio of Bi(NO3)3·5H2O, KI, and Ti3C2 is 145.5:49.8:25;

[0012] The solvents of Bi(NO3)3·5H2O solution and KI solution were both ethylene glycol;

[0013] (2) transferring the mixed solution obtained in step (1) into a high-pressure reactor, reacting at 120° C. for 24 h, then cooling to room temperature, centrifuging and washing, and vacuum drying the precipitate to obtain a BT material;

[0014] (3) mixing the BT material obtained in step (2) with BiPO4 and deionized water, ultrasonically treating (300W) for 15 min, centrifuging, and vacuum drying the precipitate to obtain a BT / BiPO4 material;

[0015] The mass ratio of BT material to BiPO4 is 1:1.

[0016] The preparation method of the BT / BiPO4 material of the present invention combines various preparation conditions within a limited range, so that the BT / BiPO4 material has better performance. Specifically, the present invention synthesizes the BT / BiPO4 material by constructing a heterojunction.

[0017] The present invention relates to a BT / BiPO4 material prepared by the above preparation method. The material has a sensitive detection characteristic for dopamine and has broad application prospects in medicine.

[0018] Therefore, the present invention also relates to a photoelectrochemical sensor for dopamine detection, which is prepared by forming a film of BT / BiPO4 material on the surface of a glassy carbon electrode; the specific preparation method is as follows:

[0019] The aqueous solution of BT / BiPO4 material is dropped onto the glassy carbon electrode and dried naturally in the air to form a film.

[0020] The concentration of the aqueous solution of the BT / BiPO4 material is preferably 4 to 10 mg / ml;

[0021] The volume of the solution added to the glassy carbon electrode is determined by the size of the glassy carbon electrode, so that the solution can completely cover the surface of the glassy carbon electrode.

[0022] The photoelectrochemical sensor of the present invention can be directly combined with dopamine. In the presence of dopamine, it can serve as an electron donor to consume the photogenerated holes generated by the BT / BiPO4 composite material, resulting in enhanced photocurrent, thereby quantitatively detecting dopamine.

[0023] Specifically, the method of using the photoelectrochemical sensor for dopamine detection is as follows:

[0024] Prepare dopamine standard solutions of different concentrations, test the photocurrent response with a photoelectrochemical sensor, and establish a standard curve of the logarithmic function of the photocurrent intensity and the concentration of the dopamine standard solution; test the photocurrent response of the sample to be tested with a photoelectrochemical sensor, substitute the measured photocurrent intensity into the standard curve, and obtain the dopamine content in the sample to be tested;

[0025] The solvents of the dopamine standard solution and the sample to be tested are both 0.1 mol / L phosphate buffer solution with a pH of 7.0 to 7.4;

[0026] The photocurrent test conditions are: external potential 0V, 300W xenon lamp light source; the photocurrent increases with the increase of dopamine content, and the dopamine content has a good linear response in the range of 0.01-10mM;

[0027] During the test, the volume of the solution added to the photoelectrochemical sensor is determined by the size of the photoelectrochemical sensor. The solution must completely cover the surface of the photoelectrochemical sensor, and the volume of the solution with different concentrations must remain unchanged.

[0028] Compared with the prior art, the present invention has the following beneficial effects:

[0029] 1. Based on BT / BiPO4 material used as photoanode for photoelectrochemical (PEC) bioanalysis.

[0030] 2. The BT / BiPO4 material prepared in the present invention has good light response, and the rapid electron transfer provides higher sensitivity for the detection of dopamine.

[0031] 3. The photoelectrochemical sensor prepared by using BT / BiPO4 material in the present invention is applied to dopamine detection and has good sensitivity and good linear response in the range of 0.01 to 10 mM. BRIEF DESCRIPTION OF THE DRAWINGS

[0032] Figure 1 : Photocurrent response curve of 4 mg / ml BT / BiPO4 material in Example 1.

[0033] Figure 2 : Photocurrent response curve of 8mg / ml BT / BiPO4 material in Example 2.

[0034] Figure 3 : The curve of the photocurrent response in Example 3 as the pH of the dopamine test system changes.

[0035] Figure 4 : Photocurrent response curve of BT / BiPO4 material to different substances in Example 4.

[0036] Figure 5: The curve of photoelectric response changing with dopamine concentration and the linear correlation coefficient diagram in Example 5.

[0037] Figure 6 : Photocurrent response curve of 10 mg / ml BT / BiPO4 material in Example 6.

[0038] Figure 7 : SEM images of BT / BiPO4 materials; a: SEM image of BT / BiPO4, b: high magnification SEM image of BT / BiPO4. DETAILED DESCRIPTION

[0039] The present invention is further described below by means of specific embodiments, but the protection scope of the present invention is not limited thereto.

[0040] In the following embodiments,

[0041] The preparation method of Ti3C2 is:

[0042] In a fume hood, add 2.5mL ultrapure water and 7.5mL hydrochloric acid to a polytetrafluoroethylene cup containing a rotor, seal it and stir it magnetically for 5min. Weigh 0.5g of LiF and add it to the polytetrafluoroethylene cup, and continue stirring for 10min. Weigh 0.5g of Ti3AlC2 and slowly add it to the above cup within 5min. Seal the polytetrafluoroethylene cup and put it into a beaker containing a small amount of water. Place the beaker on a constant temperature magnetic stirrer and heat it in a water bath for 48h at a temperature of 35℃ and a speed of 500r / min. Then, remove the sealing film of the polytetrafluoroethylene cup in the fume hood, suck the internal rotor with the external rotor, pour the liquid into the centrifuge tube, add 30mL of ultrapure water to it, close the lid and shake it evenly, and divide it evenly into 4 centrifuge tubes. Add 25mL of ultrapure water to each centrifuge tube, put the centrifuge tube into a centrifuge (3500r / min), and centrifuge it for 5min. Then take out the centrifuge tube, suck up the upper layer of liquid, and repeat the above operation. After centrifugation 8 times, collect the samples in the 4 tubes into one tube and add a small amount of ultrapure water. Pour the solution into a round-bottom flask and pass nitrogen for 30 minutes. Wrap the mouth of the flask with a nitrogen balloon and place it in an ultrasonic machine for 30 minutes. Remove the balloon, quickly transfer the solution into the centrifuge tube, and close the lid. Take an empty centrifuge tube and add water to balance it, then put it into the centrifuge with the previous centrifuge tube and centrifuge it (7500r / min) for 20 minutes. Take the precipitate in the centrifuge tube, vacuum dry it at 60℃ for 12 hours, and then grind the block solid into powder with a mortar. Take 120mg of powder. In a fume hood, add 2.5mL of ultrapure water and 7.5mL of hydrochloric acid to a polytetrafluoroethylene cup containing a rotor, seal it and stir it magnetically for 5 minutes. Weigh 350mgLiF and add it to the polytetrafluoroethylene cup, and continue stirring for 5 minutes. Slowly add the powder to the above cup within 1 minute. Seal the polytetrafluoroethylene cup and place it in a beaker containing a small amount of water. Place the beaker on a constant temperature magnetic stirrer and heat it in a water bath for 24 hours at a temperature of 35°C and a speed of 500r / min. Uncover the sealing film of the polytetrafluoroethylene cup in a fume hood, suck the internal rotor with an external rotor, pour the liquid into a centrifuge tube, add 30mL of ultrapure water to it, close the lid and shake evenly, and divide it evenly into 4 centrifuge tubes. Add 25mL of ultrapure water to each centrifuge tube, put the centrifuge tube into a centrifuge (3500r / min), and centrifuge for 5min. Then take out the centrifuge tube, suck up the upper layer of liquid, and repeat the above operation. After centrifugation 8 times, collect the samples in the 4 tubes in one tube and add a small amount of ultrapure water. Pour the solution into a round-bottom flask and pass nitrogen for 30min. Wrap the mouth of the flask with a nitrogen balloon and place it in an ultrasonic machine for 30min. Remove the balloon, quickly transfer the solution into the centrifuge tube and close the lid. Take an empty centrifuge tube, add water to balance it, and put it into a centrifuge with the previous centrifuge tube for centrifugation (7500r / min) for 20 minutes. Take the precipitate in the centrifuge tube, dry it in vacuum at 60℃ for 12 hours, and grind the block solid into powder with a mortar. Get 40mg of Ti3C2.

[0043] The preparation method of BiPO4 is:

[0044] 145.5 mg Bi(NO3)3·5H2O was placed in a beaker with deionized water (2 ml) and glacial acetic acid (1 ml), and magnetically stirred at room temperature to form a uniform and transparent solution A. 107.4 mg Na2HPO4·12H2O was dissolved in 3 ml deionized water to form solution B. Solution B was added dropwise to solution A to obtain a white precipitate. After stirring for 1 h, the slurry was transferred to a 15 mL autoclave, reacted at 160 ° C for 16 h and cooled to room temperature. The product was centrifuged and washed twice with deionized water and ethanol, respectively, and then dried at 60 ° C to obtain 70 mg BiPO4.

[0045] The glassy carbon electrode was purchased from Tianjin Aida Hengsheng Technology Development Co., Ltd., inner core material: glassy carbon; outer jacket material: polytetrafluoroethylene; terminal length: 20 mm; outer jacket length: 60 mm; glassy carbon core diameter: φ3.

[0046] Embodiment 1:

[0047] Dissolve 145.5 mg of Bi(NO3)3·5H2O and 49.8 mg of KI in a beaker containing 4 ml of ethylene glycol, and stir with a magnetic stirrer until dissolved. Keep stirring the KI solution, add the Bi(NO3)3·5H2O solution dropwise to the KI solution, stir for one hour, and obtain a yellow solution. Add 25 mg of Ti3C2 powder to the solution, ultrasonicate at 300 W of ultrasonic power for 10 minutes to obtain a mixed solution; transfer the mixed solution to a 15 ml Teflon-lined autoclave and react at 120 ° C for 24 hours. After the autoclave cools down, wash the product with water and alcohol and centrifuge it twice at 5000 rpm. Dry the precipitate in a vacuum at 60 ° C to obtain 110 mg of BT material.

[0048] Weigh 10 mg of BT material and place it with 10 mg of BiPO4 in a 10 ml centrifuge tube. Add 4 ml of deionized water to the centrifuge tube and ultrasonicate for 15 min at 300 W of ultrasonic power. Centrifuge the centrifuge tube once at 7000 r / min, and dry the precipitate under vacuum at 60 ° C to obtain 15 mg of BT / BiPO4 material.

[0049] 6 μL of 4 mg / ml BT / BiPO4 aqueous solution was dropped onto the glassy carbon electrode. After it was naturally dried in the air to form a film, the photocurrent response was tested in a phosphate buffer solution with a pH of 7.4 (test conditions: external potential 0 V, 300 W xenon lamp light source). The results are as follows: Figure 1 As shown, the photocurrent is 0.2μA.

[0050] Embodiment 2:

[0051] Dissolve 145.5 mg of Bi(NO3)3·5H2O and 49.8 mg of KI in a beaker containing 4 ml of ethylene glycol, and stir with a magnetic stirrer until dissolved. Keep stirring the KI solution, add the Bi(NO3)3·5H2O solution dropwise to the KI solution, stir for one hour, and obtain a yellow solution. Add 25 mg of Ti3C2 powder to the solution, ultrasonicate at 300 W of ultrasonic power for 10 minutes to obtain a mixed solution; transfer the mixed solution to a 15 ml Teflon-lined autoclave and react at 120 ° C for 24 hours. After the autoclave cools down, wash the product with water and alcohol and centrifuge it twice at 5000 rpm. Dry the precipitate in a vacuum at 60 ° C to obtain 110 mg of BT material.

[0052] Weigh 10 mg of BT material and place it with 10 mg of BiPO4 in a 10 ml centrifuge tube. Add 4 ml of deionized water to the centrifuge tube and ultrasonicate for 15 min at 300 W of ultrasonic power. Centrifuge the centrifuge tube once at 7000 r / min, and dry the precipitate under vacuum at 60 ° C to obtain 15 mg of BT / BiPO4 material.

[0053] 6 μL of 8 mg / ml BT / BiPO4 aqueous solution was dropped onto the glassy carbon electrode. After it dried naturally in the air to form a film, the photocurrent response was tested in a pH 7.4 phosphate buffer solution (test conditions: external potential 0 V, 300 W xenon lamp light source). The results are as follows: Figure 2 As shown, the photocurrent is 0.39μA.

[0054] Embodiment 3:

[0055] Dissolve 145.5 mg of Bi(NO3)3·5H2O and 49.8 mg of KI in a beaker containing 4 ml of ethylene glycol, and stir with a magnetic stirrer until dissolved. Keep stirring the KI solution, add the Bi(NO3)3·5H2O solution dropwise to the KI solution, stir for one hour, and obtain a yellow solution. Add 25 mg of Ti3C2 powder to the solution, ultrasonicate at 300 W of ultrasonic power for 10 minutes to obtain a mixed solution; transfer the mixed solution to a 15 ml Teflon-lined autoclave and react at 120 ° C for 24 hours. After the autoclave cools down, wash the product with water and alcohol and centrifuge it twice at 5000 rpm. Dry the precipitate in a vacuum at 60 ° C to obtain 110 mg of BT material.

[0056] Weigh 10 mg of BT material and place it with 10 mg of BiPO4 in a 10 ml centrifuge tube. Add 4 ml of deionized water to the centrifuge tube and ultrasonicate for 15 min at 300 W of ultrasonic power. Centrifuge the centrifuge tube once at 7000 r / min, and dry the precipitate under vacuum at 60 ° C to obtain 15 mg of BT / BiPO4 material.

[0057] 6 μL of 8 mg / ml BT / BiPO4 aqueous solution was dropped onto the glassy carbon electrode and dried naturally in the air to form a film. The photocurrent response was tested in phosphate buffer solutions with different pH values ​​and a DA concentration of 1 mM (pH values ​​were 5, 6, 7, 7.4, 8, 9, with an applied potential of 0 V and a 300 W xenon light source). The results are as follows: Figure 3 As shown, in the pH range of 5-8, the photocurrent increases as the pH decreases. In the range of 8-9, the photocurrent decreases as the pH increases. The photocurrent at pH 8 is the largest.

[0058] Embodiment 4:

[0059] Dissolve 145.5 mg of Bi(NO3)3·5H2O and 49.8 mg of KI in a beaker containing 4 ml of ethylene glycol, and stir with a magnetic stirrer until dissolved. Keep stirring the KI solution, add the Bi(NO3)3·5H2O solution dropwise to the KI solution, stir for one hour, and obtain a yellow solution. Add 25 mg of Ti3C2 powder to the solution, ultrasonicate at 300 W of ultrasonic power for 10 minutes to obtain a mixed solution; transfer the mixed solution to a 15 ml Teflon-lined autoclave and react at 120 ° C for 24 hours. After the autoclave cools down, wash the product with water and alcohol and centrifuge it twice at 5000 rpm. Dry the precipitate in a vacuum at 60 ° C to obtain 110 mg of BT material.

[0060] Weigh 10 mg of BT material and place it with 10 mg of BiPO4 in a 10 ml centrifuge tube. Add 4 ml of deionized water to the centrifuge tube and ultrasonicate for 15 min at 300 W of ultrasonic power. Centrifuge the centrifuge tube once at 7000 r / min, and dry the precipitate under vacuum at 60 ° C to obtain 15 mg of BT / BiPO4 material.

[0061] 6 μL of 8 mg / ml BT / BiPO4 aqueous solution was dropped onto the glassy carbon electrode and dried naturally in the air to form a film. The photocurrent response was tested in 10 ml phosphate buffer solution (pH 7.4) containing 10 μmol dopamine hydrochloride, 50 μmol lysine, 50 μmol arginine, 50 μmol urea, 50 μmol potassium chloride, 50 μmol sodium chloride, and 50 μmol magnesium chloride.

[0062] The results are as follows Figure 4As shown, the photocurrent in 10 ml phosphate buffer containing 10 μmol dopamine hydrochloride is -1.65 μA, the photocurrent in 10 ml phosphate buffer containing 50 μmol lysine is -0.3 μA, and the photocurrent in 10 ml phosphate buffer containing 50 μmol arginine, 50 μmol urea, 50 μmol potassium chloride, 50 μmol sodium chloride and 50 μmol magnesium chloride is close to 0 μA, indicating that the sensor has good selectivity and is resistant to interference from a variety of ions and biological secretions.

[0063] Embodiment 5:

[0064] Dissolve 145.5 mg of Bi(NO3)3·5H2O and 49.8 mg of KI in a beaker containing 4 ml of ethylene glycol, and stir with a magnetic stirrer until dissolved. Keep stirring the KI solution, add the Bi(NO3)3·5H2O solution dropwise to the KI solution, stir for one hour, and obtain a yellow solution. Add 25 mg of Ti3C2 powder to the solution, ultrasonicate at 300 W of ultrasonic power for 10 minutes to obtain a mixed solution; transfer the mixed solution to a 15 ml Teflon-lined autoclave and react at 120 ° C for 24 hours. After the autoclave cools down, wash the product with water and alcohol and centrifuge it twice at 5000 rpm. Dry the precipitate in a vacuum at 60 ° C to obtain 110 mg of BT material.

[0065] Weigh 10 mg of BT material and place it with 10 mg of BiPO4 in a 10 ml centrifuge tube. Add 4 ml of deionized water to the centrifuge tube and ultrasonicate for 15 min at 300 W of ultrasonic power. Centrifuge the centrifuge tube once at 7000 r / min, and dry the precipitate under vacuum at 60 ° C to obtain 15 mg of BT / BiPO4 material.

[0066] 6 μL of 8 mg / ml BT / BiPO4 aqueous solution was dropped onto the glassy carbon electrode and dried naturally in air to form a film. The photocurrent response was tested in dopamine solutions of different concentrations (0 mM, 0.01 mM, 0.1 mM, 0.25 mM, 1 mM, 5 mM, 10 mM, the solvent was pH = 7.4 phosphate buffer solution) (applied potential 0 V, 300 W xenon lamp light source).

[0067] The results are as follows Figure 5 As shown in the figure, the results show that the sensor has good sensitivity, the photocurrent intensity increases with the increase of dopamine concentration, and has a good linear response in the dopamine concentration range of 0.01-10mM, and the linear correlation coefficient R 2 =0.996.

[0068] Embodiment 6:

[0069] Dissolve 145.5 mg of Bi(NO3)3·5H2O and 49.8 mg of KI in a beaker containing 4 ml of ethylene glycol, and stir with a magnetic stirrer until dissolved. Keep stirring the KI solution, add the Bi(NO3)3·5H2O solution dropwise to the KI solution, stir for one hour, and obtain a yellow solution. Add 25 mg of Ti3C2 powder to the solution, ultrasonicate at 300 W of ultrasonic power for 10 minutes to obtain a mixed solution; transfer the mixed solution to a 15 ml Teflon-lined autoclave and react at 120 ° C for 24 hours. After the autoclave cools down, wash the product with water and alcohol and centrifuge it twice at 5000 rpm. Dry the precipitate in a vacuum at 60 ° C to obtain 110 mg of BT material.

[0070] Weigh 10 mg of BT material and place it with 10 mg of BiPO4 in a 10 ml centrifuge tube. Add 4 ml of deionized water to the centrifuge tube and ultrasonicate for 15 min at an ultrasonic power of 200 W. Centrifuge the centrifuge tube once at 7000 r / min, and dry the precipitate under vacuum at 60°C to obtain 15 mg of BT / BiPO4 material.

[0071] 6 μL of 10 mg / ml BT / BiPO4 aqueous solution was dropped onto the glassy carbon electrode. After it dried naturally in the air to form a film, the photocurrent response was tested in a phosphate buffer solution with a pH of 7.4 (test conditions: external potential 0 V, 300 W xenon lamp light source). The results are as follows: Figure 6 As shown, the photocurrent is 0.3μA.

Claims

1. A method for preparing BT / BiPO4 material, characterized in that: The steps include: (1) Bi(NO3)3·5H2O solution was added dropwise to KI solution, stirred for 1 h, and then Ti3C2 powder was added and ultrasonicated for 10 min to obtain a mixed solution; (2) transferring the mixed solution obtained in step (1) into a high-pressure reactor, reacting at 120° C. for 24 h, then cooling to room temperature, centrifuging and washing, and vacuum drying the precipitate to obtain a BT material; (3) The BT material obtained in step (2) was mixed with BiPO4 and deionized water, ultrasonicated for 15 min, centrifuged, and the precipitate was vacuum dried to obtain BT / BiPO4 material.

2. The method for preparing the BT / BiPO4 material according to claim 1, characterized in that: In step (1), the mass ratio of Bi(NO3)3·5H2O, KI and Ti3C2 is 145.5:49.8:

25.

3. The method for preparing the BT / BiPO4 material according to claim 1, characterized in that: In step (1), the solvents of the Bi(NO3)3·5H2O solution and the KI solution are both ethylene glycol.

4. The method for preparing the BT / BiPO4 material according to claim 1, characterized in that: In step (3), the mass ratio of BT material to BiPO4 is 1:

1.

5. The method for preparing the BT / BiPO4 material according to claim 1, characterized in that: In step (1) or step (3), the power of ultrasound is 300W.

6. BT / BiPO4 material obtained by the preparation method according to any one of claims 1 to 5.

7. A photoelectrochemical sensor for dopamine detection, characterized in that: The BT / BiPO4 material according to claim 6 is formed into a film on the surface of a glassy carbon electrode.

8. The method for preparing the photoelectrochemical sensor according to claim 7, characterized in that: The preparation method is as follows: The aqueous solution of BT / BiPO4 material is dropped onto the glassy carbon electrode and dried naturally in the air to form a film. The concentration of the aqueous solution of BT / BiPO4 material is 4-10 mg / ml.

9. The use of the photoelectrochemical sensor in dopamine detection as claimed in claim 7, characterized in that: The application method is as follows: Prepare dopamine standard solutions of different concentrations, test the photocurrent response with a photoelectrochemical sensor, and establish a standard curve of the logarithmic function of the photocurrent intensity and the concentration of the dopamine standard solution; test the photocurrent response of the sample to be tested with a photoelectrochemical sensor, substitute the measured photocurrent intensity into the standard curve, and obtain the dopamine content in the sample to be tested; The solvents of the dopamine standard solution and the sample to be tested are both 0.1 mol / L phosphate buffer solution with a pH of 7.0 to 7.4; The photocurrent test conditions are: external potential 0V, 300W xenon lamp light source.

Citation Information

Patent Citations

  • MXene-based bismuth-based photocatalytic composite membrane and preparation method thereof

    CN111822028A

  • Preparation method of self-energized photoelectrochemical sensor based on indium oxide / indium sulfide / cadmium indium sulfide

    CN112114014A

  • Preparation method of electrochemiluminescence sensor for rapidly detecting dopamine

    CN114813869A

  • Photoelectrochemical biosensor constructed based on MXene composite material and application thereof

    CN115728368A

  • Photoelectrochemical sensor based on 5Fe-TiO2atTpPa-1 composite material as well as preparation method and application of photoelectrochemical sensor

    CN117420186A